Traditions of Research on the Psychology of Understanding in Student Training as Part of Empirical, Sociocultural and Existential Realities of Being - V. Borzova, Tatiana; R. Chernobrodov, Evgeny (International Journal of Psychosocial Rehabilitation, 2020)
The paper examines traditions of research on the psychology of understanding in student training as part of empirical, sociocultural and existential realities of being. Three realities of being correspond to specific traditions of psychological research, methods, frameworks and types of understanding which can be referred to the educational process. The authors sought to bring content to the educational process with a view to developing understanding as the learning process and outcomes of training of university students. Understanding of student training can positively evolve in the cognitive tradition of psychological research, in the hermeneutic tradition and in the existential tradition of psychological research. The following indicators are used to record students‟ progression in the processual field of understanding: object of development (from the component “Individualobject” to the developed component “Individual-world”); the object‟s structure (from science-based knowledge to the approach towards the person‟s inner world and essential strengths); presuppositions and conditions, basic processes (from the development of empirical thinking in terms of terminologization/determinologization to the formation of theoretical thinking in terms of ontologization/deontologization); determinants of development (from verbal/representational explanations as translation, memorization and reproduction of texts to the arrival of one‟s own ways of being in society); mechanisms and driving forces (through increasing complexity of ways to develop understanding); and the outcome of the development of understanding (from understanding as knowledge to understanding as comprehension).